(untitled) (Web of Teachers: Inderscience Research, 2026)
The growing role of English as the dominant language of medicine, research, and international healthcare communication has significantly increased the importance of Medical English instruction in higher medical education. First-year medical students, particularly in non-English-speaking contexts, often face considerable linguistic and academic challenges when studying medical subjects in English. This article examines the process of teaching Medical English to first-year medical students through systematic needs analysis and curriculum design. The study aims to identify learners’ linguistic, academic, and professional needs and to propose a structured Medical English curriculum aligned with English for Specific Purposes (ESP) principles. The findings suggest that a needs-based curriculum enhances students’ motivation, medical vocabulary acquisition, and communicative competence, thereby improving their readiness for academic and clinical contexts.